ANALISIS ANTESEDEN ORIENTASI PASAR DAN PENGARUHNYA TERHADAP PEMBELAJARAN ORGANISASI UMKM DI EKS KARESIDENAN SURAKARTA - Wiyono, Wiyono; Karsono, Karsono; Dewi, Amina Sukma (Jurnal Informasi dan Komunikasi Administrasi Perkantoran, 2012)
The weakness of leaders in Small and Medium Business (UKM) in Indonesia dealing with market oriented are the low motivation of entrepreneurs, the low of leader commitment to apply market orientedmethod in his organization, and lack of training for themselves (Suliyanto, 2011). This research aimed to develop the culture of market oriented throughout the learning of organization that be done by examining the effect of customers and competitorsoriented to the learning of organization.  Respondents of this research are 300 owners or managers of UKM in the Greater of Surakarta. The technique of sampling in this research is purposive sample who has two criteria; an Indonesian and at least has two employees. The technique of analysis was done by Structural Equation Model (SEM). The result of this research shows antecedent variable; entrepreneurs? orientation, under-pressured of managers, training programs, and reward system has effect to customer orientation in Small and Medium Business (UKM).  Key words: customers oriented, competitors oriented, learning organizations